PENGEMBANGAN MEDIA ROBOT PINTAR DALAM MENINGKATKAN KECERDASAN ARITMATIKA ANAK USIA 5-6 TAHUN DI TK RIJALUL HAMDI KEC. GALANG T.A 2023-2024 - Salsa Nabila; Novita Friska (STKIP Subang, 2024)
Based on the results of observations made by researchers on students at Kindergarten Rijalul Hamdi sub-district. Galang, found that some students found it difficult and confused to understand the concept of numbers and basic calculations. Researchers found that this happened because teachers did not use varied and interesting teaching aids when teaching arithmetic concepts. As a result, children are less interested in learning. This causes the development of the cognitive aspects of young students, especially the cognitive aspects of arithmetic, which are still not well developed. This research aims to determine the development of smart robot media (ROPIN) in improving the arithmetic intelligence of children aged 5-6 years at Rijalul Hamdi Kindergarten. This research uses Research and Development (R&D) research. This research uses the ADDIE development model. The instrument used to collect data is a questionnaire given to validators, namely material expert validators and media expert validators. Interview instrument given to teachers before and after using smart robot media. Based on the validation results obtained from the material expert validator, a score of 92.0% was obtained in the range of 83% - 100% with very feasible criteria and the validation results obtained from the media expert validator, the score obtained was 98.1%, located in the range of 83% - 100 % with very feasible criteria, and the results of interviews from teachers in class B stated that smart robot media is very suitable for use in learning. Based on the criteria obtained from the two validators and the results of teacher interviews, it can be said that the development of smart robot media is declared valid and very suitable for use in early childhood learning.